Interpersonal Communication In The Dynamics Of "Friends With Benefits" Among Generation Z - Pratiwi, Nuning Indah; Maharani, Dian Putri; Arniti, Ni Ketut; Anggreswari, Ni Putu Yunita; Suparna, Putu; Haes, Putri Ekaresty (JURNAL KOMUNIKATIO, 2025)
This research aims to analyze the dynamics of interpersonal communication in friends with benefits relationships among Generation Z in the city of Denpasar. Friends with benefits relationships have become an increasingly common phenomenon in the modern era, especially among Generation Z, who are known for their more liberal approach to interpersonal relationships. With a qualitative approach and case study method, this research analysis the experiences of individuals involved in friends with benefits relationships through in-depth interviews. The focus of the research is to understand the role of interpersonal communication in building, maintaining, and managing friends with benefits relationships, including the social penetration process, as explained in the penetration theory, which is clearly seen in how individuals gradually share personal information, starting from more superficial aspects to more intimate ones. The research findings suggest the need for education on effective communication and awareness of social stigma, as well as the importance of maintaining a balance between personal freedom and emotional responsibility for a healthy relationship.